Dijabetes i gojaznost kao rezultat narušavanja homeostatskog mikrobioma. Novi podaci o etiopatogenezi dijabetesa - Nikolić, Dragan M. (Vojnosanitetski pregled, 2021)
The aetiopathology of diabetes is not fully understood. Recent studies have confirmed that microorganisms influence insulin secretion directly in the pancreas and indirectly in the gastrointestinal tract.  In a healthy body, microorganisms are part of the homeostatic microbiome and play a key role in maintaining health, digestion and metabolism. Formation of the homeostatic microbiome takes place in several stages: pregnancy and childbirth, breastfeeding, contact with family and wider environment, nutrition and sexual contacts. Many internal and environmental factors can lead to disorders of homeostatic microbiome, causing disorders of glucose homeostasis. The present document tests the hypothesis that disruption of the homeostatic microbiome play an important role in aetiopathogenesis of diabetes and obesity
Keywords: mikrobiota; dijabetes melitus; gojaznost; pankreas; gastrointestinalni sistem.